Laboratory Comparison of Rapid Antigen Diagnostic Tests for Lymphatic Filariasis: STANDARD Q Filariasis Antigen Test (QFAT) Versus Bioline Filariasis Test Strip (FTS) - Patricia M. Graves; Jessica L. Scott; Alvaro Berg Soto; Antin Y. N. Widi; Maxine Whittaker; Colleen L. Lau; Kimberly Y. Won (Tropical Medicine and Infectious Disease)
Accurate rapid diagnostic tests (RDTs) are needed to diagnose lymphatic filariasis (LF) in global elimination programmes. We evaluated the performance of the new STANDARD Q Filariasis Antigen Test (QFAT) against the Bioline Filariasis Test Strip (FTS) for detecting W. bancrofti antigen (Ag) in laboratory conditions, using serum (n = 195) and plasma (n = 189) from LF-endemic areas (Samoa, American Samoa and Myanmar) and Australian negative controls (n = 46). The prior Ag status of endemic samples (54.9% Ag-positive) was determined by rapid test (ICT or FTS) or Og4C3 ELISA. The proportion of samples testing positive at 10 min was similar for QFAT (44.8%) and FTS (41.3%). Concordance between tests was 93.5% (kappa 0.87, n = 417) at 10 min, and it increased to 98.8% (kappa 0.98) at 24 h. The sensitivities of QFAT and FTS at 10 min compared to the prior results were 92% (95% CI 88.0–96.0) and 86% (95% CI 80.0–90.0), respectively, and they increased to 97% and 99% at 24 h. Specificity was 98% for QFAT and 99% for FTS at 10 min. Both tests showed evidence of cross-reaction with Dirofilaria repens and Onchocerca lupi but not with Acanthochilonema reconditum or Cercopithifilaria bainae. Under laboratory conditions, QFAT is a suitable alternative RDT to FTS.